2015
DOI: 10.1371/journal.pone.0130314
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurements in the Human Hippocampus and Related Areas: Correspondence between Ex-Vivo MRI and Histological Preparations

Abstract: The decrease of volume estimates in different structures of the medial temporal lobe related to memory correlate with the decline of cognitive functions in neurodegenerative diseases. This study presents data on the association between MRI quantitative parameters of medial temporal lobe structures and their quantitative estimate in microscopic examination. Twelve control cases had ex-vivo MRI, and thereafter, the temporal lobe of both hemispheres was sectioned from the pole as far as the level of the splenium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Recent methods applying two-dimensional models to electrode grid recordings over the cortical surface have revealed oscillations traveling in multiple directions supporting versatile inter-regional communication and timing 13,[19][20][21][22][23] . We hypothesized that analogous grid recordings over the extensive human hippocampal surface 24,25 may reveal other versatile wave properties relevant for the flexible assimilation of its topographical connections. We also sought to understand whether wave propagation extends to low frequencies in delta (1-4 Hz) and alpha (10-15 Hz) ranges, since they may herald distinct cortico-hippocampal communications [26][27][28] .…”
mentioning
confidence: 99%
“…Recent methods applying two-dimensional models to electrode grid recordings over the cortical surface have revealed oscillations traveling in multiple directions supporting versatile inter-regional communication and timing 13,[19][20][21][22][23] . We hypothesized that analogous grid recordings over the extensive human hippocampal surface 24,25 may reveal other versatile wave properties relevant for the flexible assimilation of its topographical connections. We also sought to understand whether wave propagation extends to low frequencies in delta (1-4 Hz) and alpha (10-15 Hz) ranges, since they may herald distinct cortico-hippocampal communications [26][27][28] .…”
mentioning
confidence: 99%
“…Therefore, we were prompted to search other parameters and/or different methodological approaches to obtain quantitative data in nonhuman primates. Previous studies from our laboratory (Delgado‐González et al, 2015) determined an increase of 250% in the AC of humans compared with the AC in Macaca fascicularis using MRI. Other studies in Macaca mulatta monkeys by Chareyron et al (2012), and in humans by García‐Amado and Prensa (2012), report no interhemispheric differences in the amygdaloid volume, something we also wanted to determine.…”
Section: Discussionmentioning
confidence: 87%
“…Meanwhile, Simic et al (1997) found an inverse relationship between age and the number of neurons in CA1 and subiculum, but not in other subdivisions. Anatomically, the head and body of the hippocampus show significant volume reductions in older age, but this is not the case for the hippocampal tail (Rajah et al, 2010 (Gundersen, 1988;Gundersen et al, 1988;Delgado-González et al, 2015) for estimating neuronal volume in those cases where there was a previous selection of neurons, thus limiting the probability of sampling larger-sized ones (number-weighted); these studies used the disector technique to count the total number of particles in a precise volume (Sterio, 1984;Gundersen et al, 1988). Thus, volume-weighted estimates v v (soma)…”
Section: Discussionmentioning
confidence: 99%